Functional improvement of dystrophic muscle by repression of utrophin: let-7c interaction - Mishra, Manoj K.; Loro, Emanuele; Sengupta, Kasturi; Wilton, Steve D.; Khurana, Tejvir S. (PloS one, 2017)
Duchenne muscular dystrophy (DMD) is a fatal genetic disease caused by an absence of the 427kD muscle-specific dystrophin isoform. Utrophin is the autosomal homolog of dystrophin and when overexpressed, can compensate for the absence of dystrophin and rescue the dystrophic phenotype of the mdx mouse model of DMD. Utrophin is subject to miRNA mediated repression by several miRNAs including let-7c. Inhibition of utrophin: let-7c interaction is predicted to 'repress the repression' and increase utrophin expression. We developed and tested the ability of an oligonucleotide, composed of 2'-O-methyl modified bases on a phosphorothioate backbone, to anneal to the utrophin 3'UTR and prevent let-7c miRNA binding, thereby upregulating utrophin expression and improving the dystrophic phenotype in vivo. Suppression of utrophin: let-7c interaction using bi-weekly intraperitoneal injections of let7 site blocking oligonucleotides (SBOs) for 1 month in the mdx mouse model for DMD, led to increased utrophin expression along with improved muscle histology, decreased fibrosis and increased specific force. The functional improvement of dystrophic muscle achieved using let7-SBOs suggests a novel utrophin upregulation-based therapeutic strategy for DMD.